British library and information schools [ the research of the Department of Information Science, City University London - Bawden, David (Aslib proceedings, 2007)
he papers in this e-book reflect the research and scholarly interests of the staff of the Department of Information Science at City University London. One theme emerges strongly: the continued vitality and variety of the information science discipline. The traditional concerns of the department are well-represented in several papers: healthcare and scientific information (Khudair and Bawden; Robinson); information retrieval (MacFarlane; MacFarlane, McCann and Robertson); information organization (Rafferty and Hidderley); and legal and policy issues (Eisenschitz). These are complemented by new.